What makes pregnant workers sick: why, when, where and how? An exploratory study in the ready-made garment industry in Bangladesh - Sadika Akhter; Shannon Rutherford; Cordia Chu (BMC, 2017)
Abstract Background Bangladesh has made significant progress in reducing maternal mortality. Many factors have contributed to this; one is the socio-economic development of the country. The ready-made garment industry is at the forefront of this development creating employment for many women. However, the work environment has the potential to create health problems, particularly for vulnerable groups such as pregnant women. This paper explores perceptions of health problems during pregnancy of factory workers, in this important industry in Bangladesh. Methods This study was conducted in four factories using qualitative research methods to provide a view of pregnant workers' health risks beyond a bio-medical approach. Data was collected through in-depth interviews of pregnant workers and observations of their homes and workplaces. Further, key informant interviews with factory health care providers, government officials and employers revealed different perspectives and experiences. Data was collected in the local language (Bengali), then transcribed and analysed using a framework analysis approach. Results Female workers reported that participation in paid work created an opportunity for them to earn money but pregnancy and the nature of the job, including being pressured to meet the production quota, pressure to leave the job because of their pregnancy and withholding of maternity benefits, cause stress, anxiety and may contribute to hypertensive disorders of pregnancy. This was confirmed by factory doctors who suggested that developing hypertensive disorders during pregnancy was influenced by the nature of work and stress. The employers seemed focused on profit and meeting quotas and the health of pregnant workers appeared to be a lower priority. This study found that the government lacks the resources to understand the extent of the problem or the level of compliance with maternity related regulations. Conclusions These results indicate the vulnerability of female workers to physical and mental stress at work and associations with their health problems during pregnancy. It identifies the deficiencies of family, workplace and health service support for these pregnant workers, highlighting the urgent need for government and non-government organisations to work with this important export industry to improve health surveillance and monitoring and the enforcement of existing laws to protect the rights and conditions of pregnant women.